Tophaceous gout of the spine: a neurosurgical standpoint - Ferreira Lobão, Carlos Augusto; Bastos, Albedy Moreira; Santos, Rafael Brito; Duarte Cavalcante, Eduardo Anderson (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2014)
Objective: The study aim is to present the clinical, radiological aspects and treatment of this disease from the neurosurgical standpoint using a literature review and an illustrative case. Methods: A PubMed research was done with the terms “tophaceous gout”, “spine”, and “diagnosis”. We reviewed these articles and compared it with an illustrative case here presented. Results: According to a research done, this is the fifty-second case of tophaceous gout of the spine described in the English literature. The case and literature review presented demonstrate the difficulty in diagnosis, especially when the patient has no previous history of gout. Conclusion: It is important to consider tophaceous gout of the spine among the differential diagnoses that occur in the spine. Clinical and neurosurgical treatment may be required considering each case.
Keywords: Arthritis gout; spine; diagnosis